Airway Management Using Awake Fiberoptic in Thyroid Tumors: Case Report - Labobar, Otniel Adrians; Ratumasa, Marilaeta Cindryani Ra; Aryasa, Tjahya; Irawan, Ferry (Syntax Literate, 2025)
This case report aims to evaluate the effectiveness of the awake fiberoptic intubation (AFOI) technique in airway management for a patient with a thyroid mass. This is a descriptive case report that provides a detailed account of airway management in a patient with a thyroid mass. The subject of this study is a 47-year-old female with a thyroid mass. Data were collected through history-taking, physical examination, radiographic evaluation, and assessment using criteria such as MOANS, LEMON, and RODS to identify potential airway challenges. Anesthetic management and the intubation process were meticulously documented during surgery, including vital signs, drug administration, and the intubation procedure. The data were then presented in a narrative format, supported by preoperative clinical images, radiographic evaluation, and intraoperative monitoring. The results indicate that various airway assessment tests can predict difficult airway scenarios, and this case was successfully managed following ASA guidelines. The AFOI technique, which includes premedication, local anesthesia, and sedation, demonstrated a high success rate with minimal complications. In this case, AFOI was successfully performed via the oral route, with the patient remaining calm, awake, and cooperative throughout the procedure.